Crossing the color line : race, parenting, and culture - Reddy, Maureen T. (New Brunswick, N.J. : Rutgers University Press, 1994)
"Why do white people have vaginas?" asks Maureen Reddy's two-year-old son. "Why do boys have curly hair?" These are the questions Reddy grapples with on her journey, as a white mother of black children, toward an internalized understanding of race - particularly whiteness - and of racism. Moving from memoir to race theory, to literary analysis, to interviews with friends, Reddy places this personal journey in a broad cultural context. Reddy writes as a racial "insider" who stands outside accepted racial arrangements, a position that can afford unique insight into the many contradictions of those arrangements. She addresses attempts to cross the color line that divides blacks and whites; the meeting points of whiteness and blackness; the politics of feminism and anti-racism; loving blackness; mothering black children; racism in schools; and relationships among black and white women. Our culture is permeated by color. And whether we can sort out racial divisions will, Reddy feels, determine whether we survive as a society
Preface -- Acknowledgments -- 1. On Lines and Bridges -- 2. Starting Out -- 3. "Why Do White People Have Vaginas?" -- 4. "One Drop of Black Blood" -- 5. The Fourth R -- 6. Mothers, Daughters, Sisters, Comrades -- Notes -- Bibliography -- Index.
Includes bibliographical references (pages 185-189) and index.
Print version record.
eBooks on EBSCOhost
Keywords: Multiracial children -- United States -- Case studies; Mothers of multiracial children; Parents of multiracial children; Parent and child -- United States; Racism -- United States; Parent and child; Families; Nuclear families; Prejudices; Parent-Child Relations; Race Relations; Family; Prejudice; Nuclear Family; United States; Enfants métis -- États-Unis -- Études de cas; Mères d'enfants métissés.; Parents et enfants -- États-Unis.; Racisme -- États-Unis.; Parents et enfants; Familles; Préjugés.; SOCIAL SCIENCE -- Anthropology -- Cultural; SOCIAL SCIENCE -- Discrimination & Race Relations; SOCIAL SCIENCE -- Minority Studies; Prejudices; Nuclear families; Families; Mothers of multiracial children; Parent and child; Parents of multiracial children; Racially mixed children; Racism; United States; Rassenfrage; Interethnische Ehe; Kind; USA; Case studies